“Education Abroad” for International Student Advisors: What is the impact on their professional development? - Liu, Wei (Journal of International Students, 2019)
It is generally agreed that participating in study abroad programs, even short term, has positive impacts on students. But what would be the impact of an “education abroad” opportunity for staff members in international education? Reported in this paper is a 3-month long professional development program in a Canadian university for 52 international student advisors from 51 different Chinese institutions. Based on data from a survey and their comparative research reports, the study aims to glean the impacts of such an education abroad opportunity for international education professionals after their exposure to a different national context and different practices in international education. Findings of this study show that international comparison can serve as an effective approach to the professional development of international education professionals which enhances their historical, contextual and cultural understanding of their own work.